The Amazonic Mithology our relation with the symbology Chavin - Arbaiza Gonzales, Luz Rossana (2010)
This paper shows the relationship between the analysis of some brands of oral origin myths Amazon (Awajun) and its relation to the archaeological study of the symbology Chavin, in the taxonomic representation and identification of bats in the Raimondi Stela.